Pengaruh Motivasi Ekstrinsik dan Lingkungan Kerja Fisik Terhadap Kinerja Karyawan Pada PT. Penascop Maritim Indonesia Cabang Lampung - Zuriana; AK Yohanson (Politeknik Negeri Sriwijaya, 2021)
The purpose of this study was to see the effect of advertising and perceived value on student decision in online shopping. This study uses multiple regression analysis techniques. The data used in this study iThe objective of this study was examining the effect of the extrinsic motivation on the employee performance; examining the effect of the physical work environment on the employee performance; and, examining the effect of the extrinsic motivation and the physical work environment on the employee performance at Penascop Maritim Indonesia Inc., Lampung. The type of this study was the quantitative study through the associative method. The study was conducted in approximately four months. The number of sample used in this study was 33 employees who worked as office employees. The sampling technique used in this study was the purposive sampling. The data analysis technique used in this study was the multiple linear regression analysis. The hypothesis tests used in this study was the t test and f test. The result of this study showed that the extrinsic motivation had an effect on the employee performance; the physical work environment had an effect on the employee performance; and, the extrinsic motivation and the physical work environment had an effect on the employee performance.